Inclusion-Based Learning Management At Elementary School Katolik Krida Dharma Blora - Mulyati, Sri, Prof. Dr. Yetty Sardjono, M.Si, Dra. Dwi Haryanti, M. Hum (2013)
The objectives of research are describing the management of modified teaching material in inclusive learning in SD Katolik Krida Dharma Blora and describing the evaluation on the management of modified teaching material in inclusive learning in SD Krida Dharma Blora. Before modifying the teaching material, there are three steps to be followed: selecting, organizing, and synthesizing teaching material. The method used in this research is the qualitative.One is (1) observation, (2) indepth interview, and (3) documentation; in collecting the data the writer uses. And they are analyzed using(1) data collection, (2) data reduction, (3) data display, and (4) conclusion drawing. Technique of validating data used in this research is triangulation they are event, informant, document. The research results show that not all teaching materials to be delivered in inclusive learning needed modification. And the teaching material was modified depending on its difficulty, complexity, width and depth levels; the modified teaching material was adjusted with the children's need and ability on the basis of assessment result.